KNOWLEDGE MANAGEMENT SYSTEM PADA INSTITUT BISNIS TERKEMUKA DI INDONESIA - Tati Mardiana (Paradigma, 2010)
Institut Bisnis dan Informatika Indonesia (IBII) as a leading business institute in Indonesia has a goal of producing quality graduates who can work in the arena of business world. IBII forming units of the Capital Market Data Center (PDPM-IBII) as the development of education in the field of capital markets. Data on the capital market in PDPM-IBII Department can not properly optimized and explored so that the need for a method to manage the knowledge stored in the repository is structured to be communicated and used together as the basis for analysis to invest in the stock market. Conducted a qualitative research which is divided into three stages include: mapping knowledge management, strategy development PDPM-IBII KMS, and the development of KMS by using software Moodle as a learning management system for individual learning and knowledge sharing culture. The purpose of this research is to build a knowledge management system to support a culture of sharing knowledge (knowledge sharing) in PDPM-IBII for the development of knowledge management to enhance competitive advantage. With the KMS portal PDPM-IBII expected to facilitate the growth of knowledge sharing culture can create a competitive new knowledge, decision-making systems and means of delivery of the aspirations of electronic document storage. Keywords: knowledge management, knowledge sharing, The institut of bussiness, capital market, CMS, moodle.